Reproducibility of Quantitative Brain Imaging Using a PET-Only and a Combined PET/MR System - Lassen, Martin L.; Muzik, Otto; Beyer, Thomas; Hacker, Marcus; Ladefoged, Claes Nøhr; Cal-González, Jacobo; Wadsak, Wolfgang; Rausch, Ivo; Langer, Oliver; Bauer, Martin (Frontiers in Neuroscience, 2017)
The purpose of this study was to test the feasibility of migrating a quantitative brain imaging protocol from a positron emission tomography (PET)-only system to an integrated PET/MR system. Potential differences in both absolute radiotracer concentration as well as in the derived kinetic parameters as a function of PET system choice have been investigated. Five healthy volunteers underwent dynamic (R)-[11C]verapamil imaging on the same day using a GE-Advance (PET-only) and a Siemens Biograph mMR system (PET/MR). PET-emission data were reconstructed using a transmission-based attenuation correction (AC) map (PET-only), whereas a standard MR-DIXON as well as a low-dose CT AC map was applied to PET/MR emission data. Kinetic modeling based on arterial blood sampling was performed using a 1-tissue-2-rate constant compartment model, yielding kinetic parameters (K1 and k2) and distribution volume (VT). Differences for parametric values obtained in the PET-only and the PET/MR systems were analyzed using a 2-way Analysis of Variance (ANOVA). Comparison of DIXON-based AC (PET/MR) with emission data derived from the PET-only system revealed average inter-system differences of -33±14% (p<0.05) for the K1 parameter and -19±9% (p<0.05) for k2. Using a CT-based AC for PET/MR resulted in slightly lower systematic differences of -16±18% for K1 and -9±10% for k2. The average differences in VT were -18±10% (p<0.05) for DIXON- and -8±13% for CT-based AC. Significant systematic differences were observed for kinetic parameters derived from emission data obtained from PET/MR and PET-only imaging due to different standard AC methods employed. Therefore, a transfer of imaging protocols from PET-only to PET/MR systems is not straightforward without application of proper correction methods.